DETERMINAN PERTUMBUHAN KREDIT MODAL KERJA DI INDONESIA - Raisa Akbar (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to find out the effect of Inflation,  third party funds growth, non performing loan and  working capital loan rates on working capital loans growth. Ini the research, analysis using Error Corection Model (ECM) Eangle Granger.  Using thiis method. It cand be analyzed impact of short-term and long –term amongst dependent variabel and independent variabel with analytical techniques for correcting speed of adjustment in the short-term. Results of the research, in the short – term only working capital loan rates can’t significan on working capital loans growth. For the long –term  most of them from variabel independent significant only  working capital loan rates can’t significan on working capital loans growth in long- term. For long-term relationship, working capital loan interest rates have a not significant and negative effect , third party funds growth have and significant positive effect and inflation have a significant negative effect and Non Performing loand have a significant and positive effectKeyword  : Credit Growth, Non Performing Loans, Third Party Funds, Inflation, ECM Eangle –Granger